Structural performance monitoring and health assessment of highway bridges - Moyo, Pilate. (2008)
The research program seeks to develop a comprehensive state of the art bridge monitoring and health assessment program to complement existing BMS. Instrumentation and data interpretation form an important part of the research. This research is also expected to foster collaboration between academics, industry and government, which is necessary ingredient for a successful health monitoring program.